Promoting Broadband and ICT Access for Disabled Persons: Comparative Analysis of Initiatives in Asia-Pacific Region - Jayakar, K.; Liu, C.; Madden, Gary; Park, E. (Taylor & Francis Inc., 2015)
Despite the promise of broadband to improve the lives of persons with disabilities, there are wide disparities in access and usage between disabled and nondisabled populations. This article examines ten case studies of policies and programs promoting ICT and broadband access for persons with disabilities in the leading economies of the Asia-Pacific region, in order to identify factors behind programs that succeed on the basis of effectiveness and cost efficiency.